Sustained inflammation during human T-lymphotropic virus type 1 infection: a wildfire contributing to disease progression - Shegefti, Saina; Alaei, Mahsa; Ghahari, Nazanin; Telittchenko, Roman; Hanafi, Shahin Bolori; Isnard, Stephane; Routy, Jean-Pierre; Olagnier, David; Grevenynghe, Julien van (Frontiers in Medicine, 2025)
Human T-lymphotropic virus type 1 (HTLV-1) is a retrovirus affecting 10–20 million people worldwide. While many carriers remain asymptomatic, HTLV-1 infection can trigger intense inflammatory responses which are defined by the sustained release of pro-inflammatory cytokines and chemokines. Central to this process is the HTLV-1 encoded Tax oncoprotein, a viral regulator that drives uncontrolled inflammation by hijacking multiple cellular signaling pathways, such as the RelA/NF-κB signal transduction pathway. CD4 T-cells are the primary targets of Tax-mediated transformation, undergoing uncontrolled proliferation and significantly contributing to chronic immune activation seen in HTLV-1-associated diseases. However, highly activated CD4 T-cells are not alone in fueling this inflammatory “wildfire.” Other immune cells, including CD8 T-cells, monocytes, macrophages, dendritic cells, and neutrophils, also play critical roles in exacerbating the inflammatory milieu. These cells, in conjunction with CD4 T-cells, release a barrage of pro-inflammatory cytokines (IL-1α/β, IL-2, IL-6, IL-12, IL-17, TNF-α/β, and IFN-γ) and chemokines (MCP-1, MIP-1α/β, RANTES, MCP-3, IL-8, CXCL9, CXCL10, and CXCL11), all of which are perpetuating the cycle of immune activation and tissue damage. This hyper stimulated immune response contributes to HTLV-1 replication/dissemination and can lead to the development of adult T-cell leukemia/lymphoma (ATLL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM-TSP). Despite existing treatments aimed at controlling viral replication, the persistent inflammation in HTLV-1-infected individuals even in asymptomatic carriers (ACs) remains a major challenge, suggesting that targeting these pro-inflammatory responses may be another mandatory therapeutic strategy. In this context, this short-review focuses on the key immune responses that drive HTLV-1-associated inflammation and explores how these high pro-inflammatory responses contribute to the development of HTLV-1-related complications, including HAM-TSP, ATLL, and other associated inflammatory diseases during chronic viral infection.